Pendapatan dan kelayakan usahatani cabai rawit - Yuhanin Zamrodah; Lintar Brillian Pintakami (Journal of Agricultural Socio-Economics (JASE), 2020)
Indonesia is an agrarian country, one of which produces a chili commodity that can support the economy in this country. Chili is one type of horticulture that cannot be left by the community in everyday life. Besides that, chili farming has very good prospects. The purpose of this study was to determine the revenue, income obtained by farmers in one planting season, and the feasibility of chili farming in one season. The results obtained by the total income obtained by farmers in chili farming with an average income of Rp.35,124,800.-The total income earned by farmers in chili farming with an average income earned is Rp.25,204,800,- Chilli Farming in the Village of Kaligambir is worth the effort by looking at the R/C ratio of 2.54, which means that each expenditure of Rp.100.- will receive Rp.254.